A clinical case report of left homonymous hemianopia - Nishanee Rampersad; Shivani Naipal; Ashtaleena Bhawanibik; Siyathemba Andile Skam (African Vision and Eye Health)
Introduction: Homonymous hemianopia (HH), which refers to defects in the same half of the visual field in each eye, results from lesions that are posterior to the optic chiasm. Homonymous hemianopia may be classified as complete or incomplete depending on the characteristics of the visual field defect.